Seismic Signatures of Stellar Magnetic Activity—What Can We Expect From TESS? - Kiefer, René; Broomhall, Anne-Marie; Ball, Warrick H. (Frontiers in Astronomy and Space Sciences, 2019)
Asteroseismic methods offer a means to investigate stellar activity and activity cycles as well as to identify those properties of stars which are crucial for the operation of stellar dynamos. With data from CoRoT and Kepler, signatures of magnetic activity have been found in the seismic properties of a few dozen stars. Now, NASA’s Transiting Exoplanet Survey Satellite (TESS) mission offers the possibility to expand this, so far, rather exclusive group of stars. This promises to deliver new insight into the parameters that govern stellar magnetic activity as a function of stellar mass, age, and rotation rate. We derive a new scaling relation for the amplitude of the activity-related acoustic (p-mode) frequency shifts that can be expected over a full stellar cycle. Building on a catalogue of synthetic TESS time series, we use the shifts obtained from this relation and simulate the yield of detectable frequency shifts in an extended TESS mission. We find that, according to our scaling relation, we can expect to find significant p-mode frequency shifts for a couple hundred main-sequence and early subgiant stars and for a few thousand late subgiant and low-luminosity red giant stars.